2007
DOI: 10.1111/j.1462-2920.2006.01234.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community structure of ethanol type fermentation in bio‐hydrogen production

Abstract: Three continuous stirred-tank reactors (CSTRs) were used for H(2) production from molasses wastewater at influent pH of 6.0-6.5 (reactor A), 5.5-6.0 (reactor B), or 4.0-4.5 (reactor C). After operation for 28 days, the microbial community formed ethanol type (C), propionate type (A) and ethanol-butyrate-mixed type (B) fermentation. The H(2) production rate was the highest for ethanol type fermentation, 0.40 l (g VSS)(-1) day(-1) or 0.45 l H(2) (g COD removed)(-1). Microbial community dynamics and diversity wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
114
1
14

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 203 publications
(137 citation statements)
references
References 53 publications
(53 reference statements)
3
114
1
14
Order By: Relevance
“…Moreover, members of the genus Clostridium are originally metabolically versatile. Previous studies have shown that isolated Clostridium species are able to utilize various substrates, ranging from those with a high molecular weight and a complex structure (Lynd et al, 2002;Murashima et al, 2002) to those with a low molecular weight and a simple structure (Ren et al, 2006;Seedorf et al, 2008). For example, Clostridium acetireducens sp.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, members of the genus Clostridium are originally metabolically versatile. Previous studies have shown that isolated Clostridium species are able to utilize various substrates, ranging from those with a high molecular weight and a complex structure (Lynd et al, 2002;Murashima et al, 2002) to those with a low molecular weight and a simple structure (Ren et al, 2006;Seedorf et al, 2008). For example, Clostridium acetireducens sp.…”
Section: Discussionmentioning
confidence: 99%
“…The extracted DNA was used as the template for PCR amplification of the 16S rRNA gene. The 16S rRNA gene was amplified with a pair of universal primers: BSF8/20, 5Ј-AGAGTTTGATCCTGGCTCAG-3Ј, and PLA, 5Ј-GGTACTTAGATGTTTCAGTTC-3Ј (Invitrogen, Co., Ltd., Shanghai, China) (49). The reaction mixture (50 l) contained 10ϫ PCR buffer, 10 mmol/liter Tris-HCl, 0.2 mmol/liter deoxynucleoside triphosphate (dNTP), 2.5 U of Taq DNA polymerase, 0.5 mol/liter forward primer and 0.5 mol/liter reverse primer, and 20 ng template DNA.…”
Section: Methodsmentioning
confidence: 99%
“…and Enterobacter dominance. [68] The efficiency of biohydrogen production process is different depending on pretreatment method, dominance bacteria, substrate, and metabolic pathway. [910] With understanding metabolic pathway, the calculation of theoretical hydrogen yield is possible.…”
Section: Introductionmentioning
confidence: 99%
“…[212] Acetate-propionate pathway is another fermentation pathway that does not produce any hydrogen. [8]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation